Toxicity Assessment and Antifungal Potential of Copper(II) and Silver(I) Complexes with 1,10-Phenanthroline-5,6-dione Against Drug-Resistant Clinical Isolates of Cryptococcus gattii and Cryptococcus neoformans - Lucas Giovanini; Ana Lucia Casemiro; Larissa S. Corrêa; Matheus Mendes; Thaís P. Mello; Lucieri O. P. Souza; Luis Gabriel Wagner; Christiane Fernandes; Matheus M. Pereira; Lais C. S. V. de Souza; Andrea R. S. Baptista; Josué de Moraes; et al. (Journal of Fungi)
The World Health Organization included Cryptococcus neoformans and Cryptococcus gattii in its priority fungal pathogen list due to their high mortality rates and frequent treatment failures. These facts have driven research toward the discovery of new compounds for the treatment of cryptococcosis. In this study, we investigated the therapeutic potential of two complexes, [Cu(phendione)3](ClO4)2·4H2O (Cu-phendione) and [Ag(phendione)2]ClO4 (Ag-phendione), against drug-resistant clinical isolates of C. gattii and C. neoformans. Both complexes demonstrated anti-Cryptococcus activity, with Cu-phendione exhibiting minimum inhibitory concentration (MIC) values of 6.25 μM for C. gattii and 3.125 μM for C. neoformans, while Ag-phendione showed an MIC of 1.56 μM for both Cryptococcus species. Notably, both Cu-phendione and Ag-phendione complexes exhibited enhanced antifungal activity against reference strains of C. neoformans and C. gattii. In silico analysis identified both complexes as highly promising, exhibiting good oral bioavailability, high gastrointestinal absorption, and moderate skin permeability. Moreover, neither complex demonstrated toxicity toward sheep erythrocytes at concentrations up to 62.5 μM, with a selectivity index (SI) exceeding 10 for Cu-phendione and 40 for Ag-phendione. In vivo testing using the Galleria mellonella model demonstrated that both complexes were non-toxic, with 100% larval survival at concentrations up to 1000 μM and SI exceeding 160 following a single administration. Interestingly, larvae exposed to Cu-phendione at concentrations of 15.6–31.25 μM exhibited a significant increase in the density of hemocytes, the immune cells responsible for defense in invertebrates. Furthermore, multiple treatments with 62.5 μM of complexes caused either no larval mortality, hemocyte alterations, or changes in silk production or coloration, indicating a lack of toxicity. These findings suggest that Cu-phendione and Ag-phendione may serve as promising antifungal alternatives against Cryptococcus, with minimal host toxicity.